Microbial diversity in the critically endangered Orinoco crocodile (Crocodylus intermedius): influence of body site and Helicobacter spp. on microbiota composition - Castelli, Loreley; García-Amado, María Alexandra; Rudolf, Carla A.; Contreras, Monica; Espinosa-Blanco, Ariel S.; Godoy-Vitorino, Filipa (Frontiers in Microbiology, 2025)
IntroductionThe Orinoco crocodile (Crocodylus intermedius), a critically endangered species from Colombia and Venezuela Llanos, continues to face significant threats despite existing legal protections. Understanding the microbial diversity associated with this species, particularly in captive populations, can offer valuable insights into its health status and inform conservation strategies. In this study, we characterized the bacterial microbiota of C. intermedius, focusing on the influence of body site and the presence of Helicobacter spp. on microbial diversity.MethodsWe collected oral and cloacal samples from five captive C. intermedius individuals and analyzed their bacterial microbiota using high-throughput sequencing techniques. The study specifically investigated how microbial diversity varies by body site and how the presence of Helicobacter spp. influences community structure and composition.ResultsOral samples exhibited higher microbial diversity compared to cloacal samples. This difference is likely attributable to greater environmental exposure and dietary variation affecting the oral cavity. The presence of Helicobacter spp. was associated with a marked reduction in bacterial richness and significant shifts in community composition. Samples positive for Helicobacter spp. were notably enriched in potentially pathogenic genera, including Campylobacter and Escherichia, suggesting a dysbiotic effect on the microbiota.DiscussionOur findings indicate that both body site and Helicobacter spp. presence play significant roles in shaping the microbial communities of C. intermedius. These results have important implications for reptile health management and zoonotic disease surveillance, as dysbiosis could compromise host health and facilitate pathogen transmission. Furthermore, this study underscores the role of reptiles as potential reservoirs for Campylobacter spp. and Helicobacter spp., highlighting the need for continued research into the microbial ecology of endangered species to guide conservation strategies and inform public health policies.